The Short-Run Dynamics of the Price Adjustment to New Information - Ederington, Louis H.; Lee, Jae Ha (Journal of Financial and Quantitative Analysis, 1995)
We examine how prices in interest rate and foreign exchange futures markets adjust to the new information contained in scheduled macroeconomic news releases in the very short run. Using 10-second returns and tick-by-tick data, we find that prices adjust in a series of numerous small, but rapid, price changes that begin within 10 seconds of the news release and are basically completed within 40 seconds of the release. There is some evidence that prices overreact in the first 40 seconds but that this is corrected in the second or third minute after the release. While volatility tends to be higher than normal just before the news release, there is no evidence of information leakage. In our analysis, we correct for the biases created by bid-ask spreads and tick-by-tick data.